Aluze a citáty v české reklamě - Srpová, Hana (Stylistyka, 2000)
The analysis ofthe Czech commercials, the new type of discourse that has been influencing both life and language ofthe country lately, concentrates on that part of commercial discourse that is more attractive for consumers than others, i. e. commercials including allusions or quotations. The paper provides the factorial analysis and classifica- tion ofboth types, it enlists various sources ofthose phenomena: celebrities ofthe world culture and history (philosophers, inventors, dramatists, writers, painters etc.), stars of pop-culture, experts, company representatives, „typical satisfied consumers”, famous artifacts, fiction and the Bible, films, folk, classic and modem music, idioms etc. Sometimes they exploit even other commercials -their slogans -mostly as a parody or to state an opposition.